Penurunan Tanah Berdasarkan Hasil Uji Konsolidasi di Laboratorium - Fedriawan; Athaya Zhafirah (Jurnal Konstruksi, 2022)
Land subsidence is a geotechnical problem that is often found and cannot be avoided. Analysis of land subsidence including the amount of settlement and the length of time of settlement needs to be done to predict what will happen in the field. The impact of land subsidence is the occurrence of differential settlement which can result in damage to the road pavement structure as happened at one point of the Garut – Bungbulang Road Section. Land subsidence that occurs at that location can endanger road users because it is not safe and comfortable to pass. The purpose of this study is to determine the magnitude of the decline that occurred and in what time period the decline will be completed. The method used is soil testing in the field and in the laboratory. The test is to obtain soil parameters used in settlement analysis. Parameters used include compression index (CC), consolidation coefficient (CV), and void ratio (eo). The results obtained are land subsidence that occurs by 0.0105 m and will occur within a period of 480 years.